2022
DOI: 10.1002/ps.7305
|View full text |Cite
|
Sign up to set email alerts
|

Pannier is a key regulator of embryogenesis, pupal development and female reproduction in the insect pest Bactrocera dorsalis

Abstract: Background: Most arthropods are famous for their large reproductive capacity, with the ovary playing a vital role in the process.The study of the regulatory mechanisms of ovarian development may have the potential for a reproduction-based pest management strategy. GATA-binding transcription factors (GATAs) as important regulatory factors mediate many physiological processes, including development, immunity, insecticide resistance and reproduction. The Pannier (pnr), a member of GATA family, was confirmed to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…Other microRNA miR-311-3p was demonstrated more expressed in B. dorsalis ovaries and fat body in sexually maturating females. , Zhang, Dou, et al (2023) showed that this microRNA interacted with Endophilin B1. Repression of miR-311-3p or Endophilin B1 led to reproductive disruption .…”
Section: Impairing Female Fertilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Other microRNA miR-311-3p was demonstrated more expressed in B. dorsalis ovaries and fat body in sexually maturating females. , Zhang, Dou, et al (2023) showed that this microRNA interacted with Endophilin B1. Repression of miR-311-3p or Endophilin B1 led to reproductive disruption .…”
Section: Impairing Female Fertilitymentioning
confidence: 99%
“…Bdpnr gene is located on chromosome 2, consists of 6 exons, and encodes a protein with two conserved 50 amino acid (aa) ZnF_GATA domains (Wang, Chitsaz, et al, 2023). and Zhang, Dou, et al (2023) showed that Bdpnr −/− homozygous mutants with CRISPR-cas9 knockout were non-viable and died during embryogenesis or pupation. The heterozygotes, in contrast, reached adulthood but had non-functional ovaries (Zhang, Dou, et al, 2023).…”
Section: Impairing Female Fertilitymentioning
confidence: 99%
See 2 more Smart Citations